2019
DOI: 10.1021/acs.jced.9b00113
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Equilibrium for Binary and Ternary Phases of Saturated Fatty Acid–Urea–Alcohol in Urea Complexation

Abstract: Urea complexation is a fractionating process to separate poly unsaturated fatty acids from vegetable and animal oil, based on the capability of saturated fatty acids (SFAs) to form complexes with urea in the ethanolic solution, which generates a solid−liquid system. This research determined models which are suitable for the fatty acid, urea, and ethanol/methanol solid−liquid equilibrium. Furthermore, activity coefficients and interaction parameters between the substances involved were evaluated. Pure SFAs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The experimental data from this study showed a tendency for fatty acids to reach the highest solubility in 95% ethanol (w/w). Figure 4 compares the solubility data of fatty acids in 95% ethanol (w/w) from this study with the research conducted by Setyawardhani, et al [3]. This research studied wider range of fatty acid mole fractions to complete the data from previous research.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…The experimental data from this study showed a tendency for fatty acids to reach the highest solubility in 95% ethanol (w/w). Figure 4 compares the solubility data of fatty acids in 95% ethanol (w/w) from this study with the research conducted by Setyawardhani, et al [3]. This research studied wider range of fatty acid mole fractions to complete the data from previous research.…”
Section: Resultsmentioning
confidence: 79%
“…Alcohol is widely used for fatty acid extraction and separation through urea complexation. Previous research showed that urea was more soluble in water than alcohol, due to their polarities [3]. However, fatty acids mostly insoluble in water.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations